Penguatan Ekonomi Rumah Tangga dengan Literasi Bisnis Digital pada Masa Pandemi Covid-19 di Desa Kendung dan Medokan Ayu – Kota Surabaya - Muttaqim, Zainal; Ningsih, Fauziah Aprilia; Sholihuddin, Muh. (Vivabio: Jurnal Pengabdian Multidisiplin, 2021)
The Covid-19 pandemic has forced all aspects of community activities to adapt to the changes that occur. The prohibition of gathering or gathering is one of them, so everything must be done online and done at home. This pandemic has had a very bad impact on economic sustainability, there are many people experiencing a decrease in income due to the Covid-19 pandemic, and even many people have lost their jobs. Not to mention the people of Kendung Village, Sememi Village, Benowo Sub-district, Surabaya, and Medokan Ayu, Medokan Ayu Village, Rungkut Sub-District, Surabaya. Many people who are married have decreased income, so they experience difficulties in their household economy. Strengthening the household economy with digital business literacy during the Covid-19 pandemic in Kendung Village and Medokan Ayu Village, Surabaya City is expected to provide education about digital business so that it can be a tool in improving the household economy during the Covid-19 pandemic. The method used is interviews and action research in the form of counseling and education about digital business. The activities were carried out well and regularly, the people of Kendung and Medokan Ayu villages were very enthusiastic about wanting to know more about digital business systems/strategies.